Empirical Study of Scale Economies and Production Complementarity: The Case of Journal Publication - Baumol, William J.; Braunstein, Yale M. (Journal of Political Economy, 1977)
An empirical study applying the theory of scale economies and inter-product complementarity. Several recently formulated concepts of the theory of scale economies are examined with the aid of estimates of cost functions, using data for publishers of scientific journals. In one case the observations are shown to fall near the outer limits of the range of declining costs, implying that neither amalgamation nor breakup of firms will reduce total cost. In another case the observations fall well within the subadditive range, implying that amalgamation can provide savings. The study confirms the applicability of the new theory of scale economies.